2013
DOI: 10.3892/ol.2013.1527
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary gynecological tumors associated with Peutz-Jeghers syndrome (Review)

Abstract: Peutz-Jeghers syndrome (PJS) is an autosomal dominant disease that is characterized by gastrointestinal hamartomatous polyposis and mucocutaneous melanin spots. The tumor suppressor gene, STK11/LKB1, which is located on chromosome 19p13.3, has been reported to be responsible for this condition. PJS is complicated by benign and malignant tumors of various organs and complications from rare diseases, including sex cord tumor with annular tubules (SCTAT) and minimal deviation adenocarcinoma (MDA), which have also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 31 publications
0
49
0
1
Order By: Relevance
“…Ohta et al reported a case with sequential lesion of LEGH, LEGH with atypia, and MDA,30 supporting this concept. In addition, the tumor suppressor STK11 gene mutation has been of interest since the patients of Peutz‐Jeghers syndrome harboring its mutation have been reported to associate with LEGH, MDA, and adenocarcinoma 31. Kuragaki et al reported that 55% of MDA cases had a mutation in the STK11 gene 32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ohta et al reported a case with sequential lesion of LEGH, LEGH with atypia, and MDA,30 supporting this concept. In addition, the tumor suppressor STK11 gene mutation has been of interest since the patients of Peutz‐Jeghers syndrome harboring its mutation have been reported to associate with LEGH, MDA, and adenocarcinoma 31. Kuragaki et al reported that 55% of MDA cases had a mutation in the STK11 gene 32.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tumor suppressor STK11 gene mutation has been of interest since the patients of Peutz-Jeghers syndrome harboring its mutation have been reported to associate with LEGH, MDA, and adenocarcinoma. 31 Kuragaki et al reported that 55% of MDA cases had a mutation in the STK11 gene. 32 We also reported that STK11 may be involved in the progression of LEGH to MDA, according to a case containing mixed lesion of LEGH and MDA with the same clonality, whereas STK11 gene mutation was observed only in MDA lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with PJS, the incidence of adenoma malignum of the uterine cervix (MDA), a usually rare form of cervical cancer, is estimated at between 15% and 30%, and patients with PJS account for 10% of the total cases (49). In another study of 11 MDA tumors from patients without PJS, six had mutations in STK11 with loss of heterozygosity.…”
Section: Resultsmentioning
confidence: 99%
“…In gynecology, there has been a particular focus on sex cord tumor with annular tubules and minimal deviation adenocarcinoma (MDA). The incidence of MDA in PJS patients is estimated to be 15–30%, while up to 10% of MDA cases complicate with PJS . Kuragaki and colleagues identified six somatic STK11 mutations out of 11 MDA (55%), and suggested that the onset of MDA may be associated with the defective expression and/or post‐translational modification of the STK11 protein .…”
mentioning
confidence: 99%
“…The incidence of MDA in PJS patients is estimated to be 15-30%, while up to 10% of MDA cases complicate with PJS. 3,4 Kuragaki and colleagues identified six somatic STK11 mutations out of 11 MDA (55%), and suggested that the onset of MDA may be associated with the defective expression and/or post-translational modification of the STK11 protein. 5 In contrast, the coexistence of lobular endocervical glandular hyperplasia (LEGH) with MDA has led to the hypothesis that LEGH was a premalignant lesion of MDA.…”
mentioning
confidence: 99%